Numerical Analysis On Truss Bridge Performance Due To Structural Elements Strength Reduction - Octariasari, Hajar Dwianandha; Wahyuningtyas, Winda Tri; Ma’ruf, M. Farid (Institut Teknologi Sepuluh Nopember, 2017)
Structural element deterioration of truss bridge will change the performance of the system. Earlier identification leads to better bridge maintenance program to prevent bridge failure. A numerical analysis has been employed to truss bridge. Structural element damage was modeled by applying strength reduction on the element through reducing its cross area. Truss bridge with various single structural element strength reductions up to 20% was simulated. The bridge performance was evaluated based on the induced deflection. The results show that the onset of maximum deflection is the middle of the span and is independent of the element to which the strength reduction employed. Meanwhile, the impacted element experiences increasing moment after strength reduction